Cultural adaptation of cognitive behavioural therapy (CBT) for patients with depression and anxiety in Saudi Arabia and Bahrain: a qualitative study exploring views of patients, carers, and mental health professionals. (2019) - Algahtani, Haifa Mohammad Saleh; Almulhim, Abdullah; AlNajjar, Fatema Ali; Ali, Mazen Khalil; Irfan, Muhammad; Ayub, Muhammad; Naeem, Farooq
Abstract: Western values influence cognitive behavioural therapy (CBT) as it was primarily developed and practised in the West. As understanding the cultural context has been linked to better therapy outcomes, it has been suggested that CBT might need modification to non-Western clients' cultural backgrounds. Previously we developed a cost-effective approach to adapt CBT for clients in China and Pakistan. In this study, we applied the same methodology for local clients suffering from depression and anxiety in the Kingdom of Saudi Arabia and Bahrain. This study aimed to understand the views of patients with depression and anxiety, caregivers and mental health professionals about CBT to develop guidelines for culturally adapting CBT for depression and anxiety. We conducted semi-structured interviews with the patients ( n = 42), caregivers ( n = 11), and psychiatrists and psychologists ( n = 16). The data were analysed using a thematic framework analysis by identifying emerging themes and categories. The themes emerging from the analyses of interviews by each interviewer were compared and contrasted with those of other interviewers. The results highlighted barriers of access to and strengths of CBT while working with these patient groups. Patients and their caregivers in both countries use a bio-psycho-spiritual-social model of illness and seek help from multiple sources. Therapists emphasized the need for using local idioms, culturally appropriate translation and minor adjustments in therapy. There were no thematic differences between the two sites. These findings will be used to culturally adapt a CBT manual, which will be tested in a randomized controlled trial. Key learning aims: After reading this article, readers will be able to: (1) Understand the need for cultural adaptation of CBT. (2) Identify the necessary steps to adapt CBT for the Muslim Arab population. (3) Understand the modifications required to deliver culturally adapted CBT for the Muslim Arab population.